Within and between gender disparities in income and education benefits from democracy - Ruth Uwaifo Oyelere (Institute for the Study of Labor (IZA), 2007)
There is data evidence that welfare has improved post democracy in Nigeria. However, the distribution or concentration of the benefits in subgroups of the population is unknown. In this paper, the question of differential welfare impacts, across and within gender, post democracy in Nigeria is explored. I make use of simple econometric tools to test two null hypotheses. First, there is no disparity in the income and returns to education benefits of the shift to democracy across gender in Nigeria. Second, there are no within gender disparities of the shift to democracy on income and returns to education in Nigeria. From the results, both null hypotheses are rejected. Though men and women benefited from reforms post democracy, gender differences exist. Specifically, I find on average higher income benefits for men post democracy. Nigeria. However, disparities in income benefits are at lower levels of education. Men and women have similar income benefits at the tertiary level. Interestingly, I find the reverse when considering returns to education. On average, women experienced a greater change in returns to education post democracy in Nigeria but this disparity is primarily at the tertiary level. I also find inequality has increased post democracy in Nigeria, more so among women than men.
Keywords: O15; 330; Gender; democracy; income gap; disparities; returns to education; Nigeria; inequality; Demokratisierung; Wohlfahrtseffekt; Bildungsertrag; Einkommensverteilung; Lohndifferenzierung; Geschlechterdiskriminierung; Nigeria